High fat diet feeding exaggerates perfluorooctanoic acid-induced liver injury in mice via modulating multiple metabolic pathways. - Xiaobing Tan (Public Library of Science (PLoS), 2013)
High fat diet (HFD) is closely linked to a variety of health issues including fatty liver. Exposure to perfluorooctanoic acid (PFOA), a synthetic perfluorinated carboxylic acid, also causes liver injury. The present study investigated the possible interactions between high fat diet and PFOA in induction of liver injury. Mice were pair-fed a high-fat diet (HFD) or low fat control with or without PFOA administration at 5 mg/kg/day for 3 weeks. Exposure to PFOA alone caused elevated plasma alanine aminotransferase (ALT) and alkaline phosphatase (ALP) levels and increased liver weight along with reduced body weight and adipose tissue mass. HFD alone did not cause liver damage, but exaggerated PFOA-induced hepatotoxicity as indicated by higher plasma ALT and AST levels, and more severe pathological changes including hepatocyte hypertrophy, lipid droplet accumulation and necrosis as well as inflammatory cell infiltration. These additive effects of HFD on PFOA-induced hepatotoxicity correlated with metabolic disturbance in liver and blood as well as up-regulation of hepatic proinflammatory cytokine genes. Metabolomic analysis demonstrated that both serum and hepatic metabolite profiles of PFOA, HFD, or HFD-PFOA group were clearly differentiated from that of controls. PFOA affected more hepatic metabolites than HFD, but HFD showed positive interaction with PFOA on fatty acid metabolites including long chain fatty acids and acylcarnitines. Taken together, dietary high fat potentiates PFOA-induced hepatic lipid accumulation, inflammation and necrotic cell death by disturbing hepatic metabolism and inducing inflammation. This study demonstrated, for the first time, that HFD increases the risk of PFOA in induction of hepatotoxicity.